Dynamic trapping and manipulation of biological cells with optical tweezers - Sun, Dong (2014)
Current control techniques for optical tweezers work only when the cell is located in a small neighbourhood around the centroid of the focused light beam. Therefore, the optical trapping fails when the cell is initially located far away from the laser beam or escapes from the optical trap during manipulation. In addition, the position of the laser beam is treated as the control input in existing optical tweezers systems and an open-loop controller is designed to move the laser source. In this paper, we propose a new robotic manipulation technique for optical tweezers that integrates automatic trapping and manipulation of biological cells into a single method. Instead of using open-loop control of the position of laser source as assumed in the literature, a closed-loop dynamic control method is formulated and solved in this paper. We provide a theoretical framework that bridges the gap between traditional robotic manipulation techniques and optical manipulation techniques of cells. The proposed controller allows the transition from trapping to manipulation without any hard switching from one controller to another. Simulation and experimental results are presented to illustrate the performance of the proposed controller.